Digital experience design : ideas, industries, interaction - Leung, Linda (Changing media--changing Europe series., 2008)
Although the dot.com bubble burst long ago, the interactive media industry is still flush with fresh talent, new ideas, and financial success. Digital Experience Design chronicles the diverse histories and perspectives of people working in the dot.com world alongside an account of the current issues facing the industry. From the perspective of older disciplines such as education, fine art, and cinema, this volume investigates how dot.com practitioners balance the science of usability with abstract factors such as the emotional response design can provoke. Contributors from a wide-range of diff.